Increased exposure to sodium during pregnancy and lactation changes basal and induced behavioral and neuroendocrine responses in adult male offspring. Issue 6 (29th March 2017) - Silva, Marcia S.; Lúcio‐Oliveira, Fabiana; Mecawi, Andre Souza; Almeida, Lucas F.; Ruginsk, Silvia G.; Greenwood, Michael P.; Greenwood, Mingkwan; Vivas, Laura; Elias, Lucila L. K.; Murphy, David; Antunes‐Rodrigues, José
Abstract: Excessive sodium (Na + ) intake in modern society has been associated with several chronic disorders such as hypertension. Several studies suggest that early life events can program physiological systems and lead to functional changes in adulthood. Therefore, we investigated behavioral and neuroendocrine responses under basal conditions and after 48 h of water deprivation in adult (60‐day‐old Wistar rats) male, Wistar rats originating from dams were offered only water or 0.15 mol/L NaCl during pregnancy and lactation. Early life salt exposure induced kidney damage, as shown by a higher number of ED‐1 positive cells (macrophages/monocytes), increased daily urinary volume and Na + excretion, blunted basal water intake and plasma oxytocin levels, and increased plasma corticosterone secretion. When challenged with water deprivation, animals exposed to 0.15 mol/L NaCl during early life showed impaired water intake, reduced salt preference ratio, and vasopressin (AVP) secretion. In summary, our data demonstrate that the perinatal exposure to excessive Na + intake can induce kidney injury in adult offspring and significantly affect the key mechanisms regulating water balance, fluid intake, and AVP release in response to water deprivation. Collectively, these novel results highlight the impact of perinatal programming on the homeostatic mechanisms regulating fluid and electrolyte balance during exposure to an environmental stress (i.e. dehydration) in later life. Abstract : Our study showed that early life salt exposure can program the physiological systems and leads to functional changes in adulthood when the offspring is exposed to an environmental stress (i.e. dehydration).